TRIPS, eBay, and Denials of Injunctive Relief: Is Article 31 Compliance Everything? - Mace, Andrew; Mace, Andrew (Science and Technology Law Review, 2009)
In eBay, Inc. v. MercExchange, L.L.C., the Supreme Court held that decisions to grant injunctive relief must accord with the traditional principles of equity, thereby invalidating the practice of generally granting permanent injunctions to patentees upon finding infringement. Under eBay, denials of permanent injunctive relief might become more common, as courts instead opt to award an ongoing royalty. Because TRIPS contains provisions—primarily Article 31—that specify the conditions under which compulsory licenses for patents may be granted, an increase in denials of injunctive relief in favor of an ongoing royalty (creating, in essence, a compulsory license) in the U.S. requires review as to whether the U.S. is out of compliance with these provisions. This Note 1) examines the primary provisions relating to compulsory licensing in TRIPS; 2) studies differences of opinion regarding the nature of compulsory licenses and which understanding is appropriate for TRIPS based on a review of the Agreement‘s text and drafting history, historical practices, and policy; 3) examines eBay and subsequent cases denying permanent injunctive relief; 4) analyzes where eBay and TRIPS may conflict and attempts to resolve the differences; and 5) suggests strategies that U.S. courts might adopt to be TRIPS compliant with respect to compulsory licensing. This Note concludes that the U.S. faces a dilemma irrespective of Article 31‘s ultimate interpretation: if eBay is TRIPS compliant, developing countries can cite the case as precedent for implementing their own compulsory licensing systems with their own notions of equity and the public interest; if eBay is not TRIPS compliant, the U.S. may be brought before the TRIPS Dispute Settlement Body, the result of which would be a loosening of TRIPS compulsory licensing requirements or a re-tightening of the U.S. patent law injunctive relief. Absent a Dispute Settlement Body panel report interpreting Article 31, the WTO should issue a ministerial declaration to clarify the meaning and scope of Article 31 as it did for public health in the Doha Declaration.